2014
DOI: 10.1109/tasc.2014.2311444
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Experimental Demonstration of Adiabatic Quantum-Flux-Parametron Gates Using Quantum-Flux-Latches

Abstract: We experimentally demonstrated high-speed logic operations of adiabatic quantum-flux-parametron (AQFP) gates through the use of quantum-flux-latches (QFLs). In QFL-based high-speed test circuits (QHTCs), the output data of the circuits under test (CUTs), which are driven by high-speed excitation currents, are stored in QFLs and are slowly read out using low-speed excitation currents. We designed and fabricated three types of QHTCs using QFLs with different circuit parameters, where the CUTs were buffer gates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It is clear that through the use of RQFP gates, detailed discussion and investigations on the energy efficiency of reversible computing will become possible. Although the energy dissipation of the RQFP gate was too small to measure in the low-speed demonstration at 100 kHz, we expect that we will be able to measure it at a higher operation frequency (~1 GHz) in future work by using high-speed interface circuits31 and the superconducting resonator-based method24. Also, in previous work24, we have confirmed that calculation results of energy dissipation well agree with experimental results using superconducting resonators.…”
Section: Discussionsupporting
confidence: 75%
“…It is clear that through the use of RQFP gates, detailed discussion and investigations on the energy efficiency of reversible computing will become possible. Although the energy dissipation of the RQFP gate was too small to measure in the low-speed demonstration at 100 kHz, we expect that we will be able to measure it at a higher operation frequency (~1 GHz) in future work by using high-speed interface circuits31 and the superconducting resonator-based method24. Also, in previous work24, we have confirmed that calculation results of energy dissipation well agree with experimental results using superconducting resonators.…”
Section: Discussionsupporting
confidence: 75%
“…This allows one to reduce decoherence in the considered scheme. Experimental studies have shown that ASL circuits demonstrate ultra-high (even for superconducting circuits) energy efficiency with an increase in operating frequencies up to several gigahertz [39]. A numerical study of the dynamic processes [40] in the nSQUID allowed us to select parameters for which it is possible for the picosecond control pulses with the required shape and accuracy to pass through the ASL transmission line.…”
Section: Resultsmentioning
confidence: 99%
“…However, QFLs could realize AQFP circuits with totally new operation principles, such as the high-speed interface circuit [13] and the QXOR.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the QFL not only provides a solution to data storage in AQFP logic, but also can lead to new applications. In the previous study, we demonstrated AQFP logic circuits at 1 GHz using QFLs as high-speed interface circuits [13]. In this paper, we report a novel QFL-based XOR gate.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation